Tone 3 Sandhi in Mandarin Chinese: Phonological Rule or Process? - Liu, Nian (Journal of Sinology (วารสารจีนวิทยา), 2016)
The phenomenon of third tone (T3) sandhi in Mandarin Chinese has long been noticed: underlying full T3s may be modified under the influence of their tonal phonetic environment. By discussing in detail from the perspectives of perception, historical development and phonological domain, this paper argues that it is more convincing to take T3 sandhi as a phonological process rather than a morpho-phonological rule resulting from historical residue. This study corrects the long-time misunderstanding of Chinese tone sandhi—that all of it has originated because of historical change of tones by showing that T3 sandhi is a special phenomenon that distinguishes itself from other sandhi. Also, the conclusion has pedagogical implications which can help language learners in studying Chinese tone systems—the sandhi is not to be mechanically memorized, but can be naturally acquired. This research has implications in teaching Chinese as a second language.